Experience of collecting medicinal plants in an ethno-ecological nomadic camp - Sleptsov Yuri; Neustroeva Anna; Shergina Tuyaara; Kozhurova Alina (E3S Web of Conferences, 2023)
The article deals with the experience of nomadic ethno-ecological camp for children of Even - indigenous minorities of the North, where in addition to learning their native language, schoolchildren collect medicinal plants. A nomadic camp is a form of organising a temporary children's group in the summer for the education and upbringing of children. The creation of nomadic conditions, in-depth study of the native language in natural life conditions in the process of labour and traditional way of life, familiarisation with folk traditions, customs and rituals, transmission of ethnic culture values, study of the toponymy of the native land - all this constitutes a substantial system of pedagogical conditions, the aim and objectives of the nomadic camp's activities.